Periodontopathic microorganisms in peripheric blood after scaling and root planing - Gloria Ine´s Lafaurie (Blackwell Synergy, 2007)
Aim: The objective of this study was to evaluate the frequency of periodontopathic and other subgingival anaerobic and facultative bacteria in the bloodstream following scaling and root planing (SRP). Material and Methods: Forty-two patients with severe generalized chronic periodontitis (GChP) and generalized aggressive periodontitis (GAgP) were included in the study. Four samples of peripheric blood were drawn from the cubital vein at different times: Pre-treatment: immediately before the SRP procedure (T1), immediately after treatment (T2), 15 min. post-treatment (T3) and 30 min. posttreatment (T4). In order to identify the presence of microorganisms in blood, subcultures were conducted under anaerobic conditions. Results: 80.9% of the patients presented positive cultures after SRP and it occurred more frequently immediately after treatment; however, 19% of the patients still had microorganisms in the bloodstream 30 min. after the procedure. The periodontopathic microorganisms more frequently identified were Porphyromonas gingivalis and Micromonas micros. Campylobacter spp., Eikenella corrodens, Tannerella forsythensis, Fusobacterium spp. and Prevotella intermedia were isolated less often. Actinomyces spp. were also found frequently during bacteraemia after SRP. Conclusions: SRP induced bacteraemia associated with anaerobic bacteria, especially in patients with periodontal disease.